Spells and scones eaudiobook - Cates, Bailey (Magical Bakery Mystery, 2016)
When the bookshop next to the Honeybee Bakery hosts a signing for a Savannah radio celebrity's new self-help book, magical baker Katie Lightfoot is happy to provide some delectable desserts. The whole spellbook club is going to the event, curious about the book (and maybe to sample some goodies), but the final chapter comes too soon for the author when she is found dead at the event. The prime suspect is Angie Kissel, a former witch whose familiar was once Katie's own terrier, Mungo. Katie is at first hesitant to help, afraid of losing the little dog who has become so important to her. But after a little nudge from Mungo himself, Katie decides to try to conjure up the real killer—before Angie gets served.